1980
DOI: 10.1111/j.1471-4159.1980.tb07860.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Distribution of Acetylcholinesterase Molecular Forms in a Murine Neuroblastoma × Sympathetic Ganglion Cell Hybrid Cell Line

Abstract: Studies were carried out on the polymorphism of acetylcholinesterase (AChE, EC 3.1.1.7) in a neuroblastoma x sympathetic ganglion cell hybrid cell line (T28) and its parental clone (N18TG2). These cells contain the tetrameric (G4, 10S), dimeric (G2, 6.5S) and monomeric (G1, 4S) forms of AchE, but not the collagen-tailed A12(16S) form of the sympathetic ganglion. Three variants of these forms could be distinguished on the basis of their solubility properties: (i) secreted forms which do not interact with the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
0

Year Published

1982
1982
2005
2005

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(32 citation statements)
references
References 39 publications
6
26
0
Order By: Relevance
“…Previous work on this cell line (Johnson and Moore, 2000) has shown that there are no high salt-soluble isoforms present. These results on the distribution of AChE isoforms confirm others on neuroblastoma cell lines (Kimhi et al, 1980;Lazar and Vigny, 1980;Melone et al, 1987;Stieger et al, 1989). The increase in AChE levels seen on differentiation is well documented, and is frequently used as a differentiation marker in many cell types.…”
Section: Discussionsupporting
confidence: 88%
“…Previous work on this cell line (Johnson and Moore, 2000) has shown that there are no high salt-soluble isoforms present. These results on the distribution of AChE isoforms confirm others on neuroblastoma cell lines (Kimhi et al, 1980;Lazar and Vigny, 1980;Melone et al, 1987;Stieger et al, 1989). The increase in AChE levels seen on differentiation is well documented, and is frequently used as a differentiation marker in many cell types.…”
Section: Discussionsupporting
confidence: 88%
“…There is no chemical or structural basis for a difference in substrate affinity: butyrylcholine is simply a larger molecule that cannot access the more constrained active site of AChE. These results on neuroblastoma AChE and BChE levels, both cell-associated and in the medium, confirm those of other workers [45][46][47].…”
Section: Discussionsupporting
confidence: 79%
“…However, quantitative comparisons of ChE activity levels between NTera 2 cells and other tissue sources are difficult, since NTera 2 cells show varying levels of ChE when grown at different densities (data not shown). Such variation in ChE levels is also seen in cultured murine neuroblastoma cells and may reflect density-dependent differences in mitotic activity (Blume et al, 1973;Schneider, 1993;Vimard et al, 1993;Kimhi et al, 1980;Lazar and Vigny, 1980;Chang and Blume, 1976).…”
Section: Cholinesterase Is Expressed In Undifferentiated and Differenmentioning
confidence: 93%